SOFTWARE ECOSYSTEM AS A SYSTEM OF SYSTEMS - Гріненко, О.О. (Science-based technologies, 2014)
The paper deals with the problem of modeling software ecosystems and their formal description and presentation software ecosystem as a system of systems. Under the system of systems is considered any system which consists of systems that are themselves autonomous. Under the system we mean any set of interacting or interdependent entities forming purposeful unity. Under autonomy we mean the ability to exercise independent action or decision. So the software ecosystem can be viewed as a system of systems, autonomous components of which will be following: software (technical abstract system); hardware (technical material system); natural objects and phenomena (natural system); State, standards bodies, developers and sellers, software users (economic system); developers and managers, social groups (social system). Formally to describe each component of the system is proposed by the following theories: set theory and algebraic operations on them; relations theory; propositional logic and real-time process algebra (RTPA).